2014
DOI: 10.1177/1362361314520755
|View full text |Cite
|
Sign up to set email alerts
|

Misinterpretation of facial expressions of emotion in verbal adults with autism spectrum disorder

Abstract: Facial emotion perception is significantly affected in autism spectrum disorder (ASD), yet little is known about how individuals with ASD misinterpret facial expressions that result in their difficulty in accurately recognizing emotion in faces. This study examined facial emotion perception in 45 verbal adults with ASD and 30 age- and gender-matched volunteers without ASD to identify patterns of emotion misinterpretation during face processing that contribute to emotion recognition impairments in autism. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 41 publications
6
52
1
2
Order By: Relevance
“…Kuusikko and colleagues (2009) found that youth with ASD were more likely than peers without ASD to perceive ambiguous faces as portraying negative emotions, suggesting biased interpretations. Eack et al (2014) similarly found that adults with ASD perceived neutral faces as negative whereas typically developing adults did not. In summary, in the presence of atypical visual attending to the environment ‐ specifically aversion to social stimuli and bias toward threat cues, ER impairments may be expressed as anxiety.…”
Section: Overview: Emotion Regulation and Anxiety In Asdmentioning
confidence: 80%
“…Kuusikko and colleagues (2009) found that youth with ASD were more likely than peers without ASD to perceive ambiguous faces as portraying negative emotions, suggesting biased interpretations. Eack et al (2014) similarly found that adults with ASD perceived neutral faces as negative whereas typically developing adults did not. In summary, in the presence of atypical visual attending to the environment ‐ specifically aversion to social stimuli and bias toward threat cues, ER impairments may be expressed as anxiety.…”
Section: Overview: Emotion Regulation and Anxiety In Asdmentioning
confidence: 80%
“…It has been shown that emotion processing in adolescents is similar to adults but not quite mature yet [74]. While some previous studies [3, 75] did not find impairment in emotion recognition in adolescents, a number have noted impairment even in adults with ASD [76, 77]. Additionally, Kuusikko et al [78] noted that older youth (12 and up) with ASD differed more from their typical peers in FER ability than younger youth with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of social skills programs have been developed for autistic adults, under the assumption that improving social understanding and ability will improve functional outcomes [Eack et al, 2013;Spain & Blainey, 2015]. Because autistic adults without intellectual disability often perform poorly on measures of social cognition [Morrison et al, 2019;Velikonja, Fett, & Velthorst, 2019], including in the areas of social attention [Pelphrey et al, 2002;Sasson et al, 2007], affect recognition [Eack, Mazefsky, & Minshew, 2015], and advanced theory of mind [Baron-Cohen, Jolliffe, Mortimore, & Robertson, 1997], programs often focus on social cognition and explicitly teach strategies for improving performance Kandalaft, Didehbani, Krawczyk, Allen, & Chapman, 2013;Koegel, Ashbaugh, Navab, & Koegel, 2016;Turner-Brown, Perry, Dichter, Bodfish, & Penn, 2008]. Indeed, these programs often do improve performance on specific tasks [Bishop-Fitzpatrick, Minshew, & Eack, 2014;Kandalaft et al, 2013;Koegel et al, 2016], and confer other benefits like increasing knowledge about social skills [Gates, Kang, & Lerner, 2017] and facilitating friendship development when a peer group component is included [Spain & Blainey, 2015].…”
Section: Introductionmentioning
confidence: 99%